The effectiveness of solution-based therapy on negative meta-emotions and symptoms of body dysmorphic disorder in cosmetic surgery applicants - Mirzaei, Zahra; Heydari , Zahra; Pourdanesh, Fahimeh Alsadat; Homaei , Fatemeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: This study aimed to determine the effectiveness of solution-oriented therapy on negative meta-emotions and body dysmorphic symptoms in cosmetic surgery applicants. Method: This research was quasi-experimental, with a pre-test, post-test and control group design with a two-month follow-up phase. The statistical population included all surgical applicants who had visited beauty clinics in the city. The statistical sample included 30 of these applicants who were selected purposefully. Then, 15 people were randomly placed in the control group and 15 people in the experimental group. The intervention group received solution-oriented therapy during 8 sessions of 90 minutes once a week. The data were collected using Meta-Emotions Scale (MES) (2009) and Body Image Concern Inventory (BICI) (2005) and analyzed by variance analysis with repeated measurements. Results: The results showed that the main effect of the group was significant for negative meta-emotions (F=94.2, P>0.05, P>0.771) and for body dysmorphic disorder symptoms (F=12.9, P>0.05, 315/315). In the negative meta-emotions variable, the main effect of the three stages of pre-test, post-test and follow-up (P<0.05, P<0.05, F=13.5) was significant. It was also reported as significant in the variable of body dysmorphic symptoms (P>0.05, P>0.05, F=6.37). Conclusion: It can be concluded that solution-oriented therapy is effective in negative meta-emotions and body dysmorphic disorder symptoms. Therefore, they can be useful for cosmetic surgery applicants.